Effects of air temperature, relative humidity, air velocity and orientation towards occupants’ satisfaction in low-cost detached houses / Noor Anis Afifa Shamsu Kamal Bahrin - Shamsu Kamal Bahrin, Noor Anis Afifa (2022)
Thermal comfort is an important factor in ensuring a house's good thermal condition, affecting people’s productivity. People spend almost 90% of their time inside the house than outside. Since most people spend most of their time indoors, there is constant and complex contact between the inhabitants and their surroundings, affecting them physiologically and psychologically. Therefore, the thermal comfort in a residential building must be considered carefully. Several thermal comfort parameters need to be measured to understand the current indoor thermal situation of typical low-cost single-storey detached houses in Malaysia. This study aims to identify the effects of the thermal comfort condition and orientation towards occupants’ satisfaction in low-cost detached houses. There are three objectives for this study: 1) To measure the thermal comfort condition in low-cost detached houses, 2) To determine the occupants’ satisfaction towards thermal comfort condition in low-cost detached houses, and 3) To analyse the relationship between thermal comfort condition, orientation, and occupants’ satisfaction in low-cost detached houses.